METHODS OF ASSESSING THE ADEQUACY OF THE RESULTS DELIMITATION OF FIRE RESISTANCE OF REINFORCED CONCRETE BEAMS EXPERIMENTAL AND COMPUTATIONAL METHODS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The method is developed to estimate the correctness of approach of fire resistance. This approach combines the fire tests of the beams without the application of mechanical loads and further interpretation of the temperature measurements. Keywords:fire tests, fire resistance, fire-resistance, reinforced concrete beam, bearing capacity, interpretation, adequacy.